Correlates Of Delayed Initiation of Treatment After Confirmed Diagnosis Under RNTCP: A Cross Sectional Study in Ahmedabad Municipal Corporation, India - Patel, Punit G; Bala, D V; Vagela, Snehal D (National Journal of Community Medicine, 2013)
Purpose: Tuberculosis in India accounts for 1/3rd of global burden. Initiation of treatment by the health system is an essential step. The aim of this study was to assess delay in the treatment in AMC area. Methodology: All smear positive patients who had treatment delay were identified from 10TUs of AMC who had started treatment between 1stOctober 2010 and 30thSeptember 2011. Out of total 204, 14 had migrated and 30 had initiated treatment during hospitalization soon after diagnosis were excluded. Therefore, 160 patients were interviewed in DOTS centre or in their homes using predesigned and pretested questionnaire. Results: Mean age was 37.3+14.6 years and 69(43.1%) were in the 26 to 45 age group. About 114(71%) were male. Category I, II and IV Tuberculosis patients were 38.7%, 61.2%, and 0.06% respectively. The median duration for treatment delay was 14 days (range 8 to 90). Factors responsible for delayed initiation of treatment included health system delay (36.8%), personal reasons (92.5%) and both (28.7%). Important factors of treatment delay were social (34%) followed by adverse effects of drugs (32%) and referral delay from another TU (29%). After adjusting various factors like gender (female) and lower socio-economic class, personal reasons emerged as significant determinants for treatment delay more than 14 days. Conclusion: Present As demonstrated in this study, significant factors were lower socio-economic class, personal reasons and female sex, these factors must be taken into account while giving health education. Sound referral system can also minimize treatment delay.